2010
DOI: 10.1021/jo101769d
|View full text |Cite
|
Sign up to set email alerts
|

Iron-Mediated Radical Halo-Nitration of Alkenes

Abstract: Radical halo-nitration of alkenes using iron(III) nitrate nonahydrate and halogen salt has been developed. The present reaction proceeds by radical addition of nitrogen dioxide generated by thermal decomposition of iron(III) nitrate nonahydrate and subsequent trapping of the resultant radical by a halogen atom in the presence of halogen salt. Application of this method to synthesis of nitroalkenes is also described. The practicality of the present method using nontoxic and inexpensive iron reagents has been sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(42 citation statements)
references
References 67 publications
0
40
1
1
Order By: Relevance
“…2 In addition, Fe(NO 3 ) 3 ·9H 2 O is well-known to produce NO 2 radical on heating; 3,4 however, its application in synthetic chemistry is limited (Scheme 1a). 5 In continuation of our studies on bisarylhydrazones, 6 we report here an Fe(NO 3 ) 3 ·9H 2 Omediated radical nitration of bisarylsulfonyl hydrazones at moderate temperature (Scheme 1b). The broad substrate scope, use of nontoxic iron salt as the nitro source, and the readily accessible aryl aldehydes and arylsulfonyl hydrazides as the substrate precursors are the significant practical features.…”
Section: ■ Introductionmentioning
confidence: 52%
“…2 In addition, Fe(NO 3 ) 3 ·9H 2 O is well-known to produce NO 2 radical on heating; 3,4 however, its application in synthetic chemistry is limited (Scheme 1a). 5 In continuation of our studies on bisarylhydrazones, 6 we report here an Fe(NO 3 ) 3 ·9H 2 Omediated radical nitration of bisarylsulfonyl hydrazones at moderate temperature (Scheme 1b). The broad substrate scope, use of nontoxic iron salt as the nitro source, and the readily accessible aryl aldehydes and arylsulfonyl hydrazides as the substrate precursors are the significant practical features.…”
Section: ■ Introductionmentioning
confidence: 52%
“…Runs 1–3 showed that Fe(NO 3 ) 3 ⋅ 9H 2 O is an effective reagent for the nitration of pyrazolin‐5‐one 1 a at 60–80 °C, but at room temperature 4‐nitropyrazolin‐5‐one 2 a was obtained in a yield of only 33 % (run 4). Apparently, an elevated temperature was necessary for the decomposition of Fe(NO 3 ) 3 ⋅ 9H 2 O and the release of the active nitrating agent NO 2 . The introduction of NaNO 2 into the reaction allowed the room‐temperature nitration of pyrazolin‐5‐one 1 a in high yields (runs 5–7).…”
Section: Resultsmentioning
confidence: 99%
“…Both hydrogen‐atom abstraction and addition to double C=C bonds are typical reactions of NO 2 . For nitration reactions mediated by iron(III) nitrate, the NO 2 free radical was previously suggested to be the active nitration agent …”
Section: Resultsmentioning
confidence: 99%
“…[2] In the field of nitrogencentered radicals, nitrogen dioxide has recently been used for the halonitration of alkenes by Taniguchi et al, [3] and Studer et al [4] reported hydroamination reactions with Naminated dihydropyridines. Among the reagents suitable for trapping radicals at their nitrogen atoms, sulfonyl azides [5] and arenediazonium salts [6] have received most attention over the last decade.…”
mentioning
confidence: 99%